Legal Strength of Grant Deed for Adopted Children - Kahar Muzakir (Sekolah Tinggi Agama Islam Taruna Surabaya, 2022)
This study wants to answer how the juridical strength of the grant deed for adopted children is in the case of the XXX/Pdt.G/2012/MS-Aceh case concerning the Cancellation of Grants. A grant is a gift made by a person to another party that is carried out while still alive and its implementation is carried out while the grantor is still alive. Grants in any law are essentially non-cancellable, unless certain conditions are met the grant can be cancelled. By using the juridical normative method, the research found that grants for adopted children normatively through a grant deed No. 04/V/2007 are valid and have legal force, because they have fulfilled the requirements in the grant agreement both formally and materially. The decision to cancel the grant in case Number XXX/Pdt.G/2012/MS-Aceh is in accordance with applicable law. The judge considers that adopted children in Indonesia have the same status as biological children, so what applies to biological children also applies to adopted children.